Quantum dots : optics, electron transport, and future applications - Tartakovskij, Aleksandr Georgijevič (Cambridge, U.K. ; New York : Cambridge University Press, 2012)
"A comprehensive review of cutting-edge solid state research, focusing on its prominent example - quantum dot nanostructures, this book features a broad range of techniques for fabrication of these nano-structured semiconductors and control of their quantum properties. Written by leading researchers, the book considers advanced III-V and II-VI semiconductor quantum dots (QDs) realized by self-assembly, lithography and chemical synthesis; novel QD structures in nanowires and graphene; and transport and optical methods for control of single QDs"
Nanostructure design and structural properties of epitaxially grown quantum dots and nanowires -- Manipulation of individual quantum states in quantum dots using optical techniques -- Optical properties of quantum dots in photonic cavities and plasmon-coupled dots -- Quantum dot nano-laboratory: magnetic ions and nuclear spins in a dot -- Electron transport in quantum dots fabricated by lithographic techniques from III-V semiconductors and graphene -- Single dots for future telecommunications applications.
Obsahuje bibliografie a rejstřík
Elektronická reprodukce.
Keywords: nanostruktury; kvantové tečky; polovodiče; nanostructures; quantum dots; semiconductors; e-knihy online; e-books online